Childhood trauma and gambling disorder: a complex association - Horak, Natascha Simone (My University, 2018)
Background: Exposure to trauma during childhood is associated with mental illness in adulthood. Numerous studies have demonstrated an increased rate of self-reported childhood trauma in substance-abusing individuals. However, there is a limited amount of research investigating whether similar links are present in behavioural addictions such as gambling disorder (GD). There is an association between childhood trauma and GD, but further research is needed to elucidate this seemingly complex association. The way in which stressful life events influence the relationship between childhood trauma and GD is also not clear. Method: Thirty-one patients with GD and 31 age- and gender-matched healthy controls from the Western Cape, South Africa, completed the Childhood Trauma Questionnaire (CTQ-SF) to assess the nature (i.e. subtypes) and severity of self-reported childhood trauma. Past 12month stressful life events were measured using the Life Event Stress Scale (LESS). It was hypothesized that childhood trauma, particularly emotional neglect and physical neglect, would be significant predictors of group membership (i.e. the presence of a primary diagnosis of GD) and GD severity. It was further postulated that stressful life events would moderate the relationship between childhood trauma and GD. Results: Severity of self-reported childhood trauma in general, as well as its five subtypes, was significantly higher in GD patients compared to healthy controls (ranging from p < .001 to p = .033). Self-reported childhood trauma was a significant predictor of a diagnosis of GD (OR = 1.22, 95% CI [1.09, 1.37], p = .001). However, no significant association was found between childhood trauma and GD severity. Of the five subtypes of childhood trauma, physical neglect was the only significant predictor of a diagnosis of GD (OR = 1.88, 95% CI [1.08, 3.27], p = .025). Results further suggested that stressful life events act as a moderator of the relationship between childhood trauma and the presence of GD (F(1,25) = 7.082, p = .01). High levels of stressful life events in the past 12 months increased the likelihood of a diagnosis of GD, independent of the severity of childhood trauma experienced. Conclusion: There seems to be a strong association between childhood trauma and GD. Neglect in childhood may have a stronger influence on the development of GD than other subtypes of childhood trauma and therefore warrants further investigation. The association between childhood trauma and GD appears to be influenced by recent stressful life events in that high levels of stress increase the likelihood of GD, independent of the severity of childhood trauma. Results highlight the importance of an integrated treatment approach which considers (childhood) trauma, but also current stress in the context of GD.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in Clinical Psychology, Johannesburg 2018
Keywords: Psychic trauma in children--South Africa; Post-traumatic stress disorder in children--South Africa; Gambling--South Africa--Psychological aspects